Financial Literacy Meets Lifestyle: Understanding the Behavioral Pathways to Effective Financial Management Among Generation Z - Endang Supriatna; Disman Disman; Eeng Ahman; Amir Machmud; Nofriansyah Nofriansyah; Ramdan Nugraha (Yayasan Keluarga Guru Mandiri, 2026)
This study examines the structural relationships among financial literacy, lifestyle, and financial management behavior among Generation Z university students in Indonesia, addressing concerns about weak financial decision-making amid increasing digital consumption and lifestyle-oriented spending. A quantitative explanatory design was employed, involving 250 undergraduate students selected through purposive sampling. Data were collected using a structured questionnaire and analyzed using partial least squares structural equation modeling (PLS-SEM). The findings indicate that financial literacy has a significant positive effect on financial management behavior both directly and indirectly through lifestyle, confirming lifestyle as a key mediating variable. This result reinforces that financial knowledge alone is insufficient unless it is internalized into daily lifestyle patterns that guide financial decisions. This study contributes theoretically by positioning lifestyle as a behavioral transmission mechanism linking financial literacy to financial management behavior, thereby extending behavioral finance and planned behavior perspectives in a Generation Z context. In practice, the findings offer insights for designing holistic financial education programs that integrate financial knowledge with lifestyle-oriented and behaviorally tailored interventions for digitally native youth.